Interaction of Giant Unilamellar Vesicles with the Surface Nanostructures on Dragonfly Wings - Cheeseman, Samuel (Langmuir : the ACS journal of surfaces and colloids, 2019)
The waxy epicuticle of dragonfly wings contains a unique nanostructured pattern that exhibits bactericidal properties. In light of emerging concerns of antibiotic resistance, these mechano-bactericidal surfaces represent a particularly novel solution by which bacterial colonization and the formation of biofilms on biomedical devices can be prevented. Pathogenic bacterial biofilms on medical implant surfaces cause a significant number of human deaths every year. The proposed mechanism of bactericidal activity is through mechanical cell rupture; however, this is not yet well understood and has not been well characterized. In this study, we used giant unilamellar vesicles (GUVs) as a simplified cell membrane model to investigate the nature of their interaction with the surface of the wings of two dragonfly species, Austrothemis nigrescens and Trithemis annulata, sourced from Victoria, Australia, and the Baix Ebre and Terra Alta regions of Catalonia, Spain. Confocal laser scanning microscopy and cryo-scanning electron microscopy techniques were used to visualize the interactions between the GUVs and the wing surfaces. When exposed to both natural and gold-coated wing surfaces, the GUVs were adsorbed on the surface, exhibiting significant deformation, in the process of membrane rupture. Differences between the tensile rupture limit of GUVs composed of 1,2-dioleoyl- sn-glycero-3-phosphocholine and the isotropic tension generated from the internal osmotic pressure were used to indirectly determine the membrane tensions, generated by the nanostructures present on the wing surfaces. These were estimated as being in excess of 6.8 mN m-1, the first experimental estimate of such mechano-bactericidal surfaces. This simple model provides a convenient bottom-up approach toward understanding and characterizing the bactericidal properties of nanostructured surfaces